Continuing midwifery education beyond graduation: Student midwives' awareness of continuous professional development. (May 2017) - Embo, M.; Valcke, M.
Abstract: Midwifery education plays an important role in educating graduates about engaging in continuous professional development (CPD) but there is a lack of empirical research analysing student midwives' awareness of CPD beyond graduation. We aimed to explore student midwives' awareness of the need to become lifelong learners and to map their knowledge of CPD activities available after graduation. Therefore, forty-seven reflective documents, written in the last week of student midwives' training programme, were analysed in a thematic way. Content analysis confirmed student midwives' awareness of the importance of CPD before graduation. They mentioned different reasons for future involvement in CPD and described both, formal and informal CPD-activities. Respondents were especially aware of the importance of knowledge, to a lesser degree of skills-training and still less of the potential value of the Internet for individual and collective learning. Respondents perceived a need for a mandatory preceptorship. Supporting learning guides were highly valued and the importance of reflection on CPD was well-established. This could have resulted from an integrated reflective learning strategy during education. Conclusion: Undergraduate midwives are aware of the importance of CPD and the interplay of formal and informal learning activities. Virtual learning requires special attention to overcome CPD challenges.